تنفيذ طريقة تدريس الأقران في تعزيز فعالية تعلم اللغة العربية لطلاب مدرسة الابتدائية تشو-أيرونج في ناراثيوات، تايلاند: Implementing the Peer Teaching Method to Enhance the Effectiveness of Learning Arabic Language for Students at Chuo-Airon Elementary School in Narathiwat, Thailand - Mualim Wijaya; Asviatul Maufiroh; Amal Ahmed Muhammed Al Anesi (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2024)
The research aims to measure the enhancement of students' interest in learning the Arabic language at Chuo-Airon Elementary School in Narathiwat, Thailand. The teaching method the teacher uses is dull and lacks variety, leading to students' boredom and difficulty understanding Arabic. The research methodology employed is analytical descriptive using a field research approach. Data sources include teachers and students, with data collection tools comprising observation, interviews, and documents. Data were analyzed through data summarization, presentation, and conclusion extraction. The research findings indicate that peer teaching effectively promotes students' interest in learning Arabic and shapes learning and teaching activities. These results are expected to positively contribute to the development of Arabic language learning methods at Chuo-Airon Elementary School.